The importance of service culture for institutional work in medical tourism: The Role of Medical Doctors / Norzayana Yusof and Herwina Rosnan - Yusof, Norzayana; Rosnan, Herwina (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Extant studies in service-dominant (SD) logic put emphasis on the need to develop mid-range theories to bridge the gap between theoretical abstraction and empirical findings. While institutions are integral to midrange-theoretical advancement, little is known about how organisations deal with it. Additionally, present research in medical tourism has been focusing on private hospitals leaving the role of medical doctors with less attention. In view of the gap, this article briefly states the institutional types that constrain value co-creation in Malaysian medical tourism. Subsequently, the institutional work for medical doctors as derived from the expectations of other stakeholders is given a thorough discussions. Thus, two direct observations were held and a total of 13 semi-structured interviews were conducted with private hospitals, medical doctors, government section, and medical tourism facilitators. Interpretive analysis was done with the assistance of ATLAS.ti. Hence, the study derived seven institutions and the specific institutional work describing how medical doctors can improve their communication and collaboration with service providers and health travellers. This paper contributes to bridging the gaps in the mid-range theory of institutions by focusing on communication and collaboration. Additionally, medical doctors could improve their service exchange with other stakeholders through the suggested institutional work provided. Considering their integral role in treating patients, this article is important for service providers in crafting their strategies to optimise their service offerings.